On the DIBL Reduction Effect of Short Channel Carbon Nanotube Field Effect Transistors - Khial Aicha; Rechem Djamil; Azizi Chrifa; Zaabat Mourad (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The Drain Induced Barrier Lowering (DIBL), in carbon Nanotubes-Fet (CNTFETS), is a challenging study that still needs investigation. Based on a numerical model, the Non-Equilibrium Green’s Function (NEGF) approach was applied to simulate the DIBL effect in CNTFETS. In this study,  the effect of the length gate ranging from 10 to 30 nm, for different temperatures (77K, 15K, 300K and 400K) on the DIBL was investigated. Then the variation of DIBL effect as a function of the nanotubes diameter varying over the following chiralities: (13, 0), (16, 0), (19, 0), (23, 0) and (25, 0) was undertaken. Afterworlds, we conducted the variation of DIBL impact as a function of the oxide thickness with the values: 1.5 nm, 3 nm, 4.5 nm, 6 nm and 7 nm. Moreover, the DIBL effect was carried at depending upon the high-k materials such as:  SiO_2, HfO_2, ZrO_2, 〖Ta〗_2 O_2 and TiO_2. Finally, a conclusion is made basing at the different findings which revealed that the best reduce of DIBL impact was recorded under a liquid Nitrogen temperature of 77 K.